2014
DOI: 10.1590/s0102-86502014001900009
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive analgesia effects of Ketamine in patients undergoing surgery. A meta-analysis

Abstract: CONCLUSIONS:Ketamine was able to accomplish some preemptive analgesic effects of reducing postoperative morphine consumption and prolonging the time to first analgesic. Meanwhile, ketamine was as safe as physiological saline in side effects of nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
2
16
1
2
Order By: Relevance
“…The optimal dose and infusion timing of ketamine for postoperative pain control has not yet been established; however, most trials have used ketamine in subanesthetic doses during the perioperative period. [18] Reviews and meta-analyses that have evaluated the preemptive analgesic effects of ketamine for postoperative pain have concluded that subanesthetic doses of ketamine (0.15–0.5 mg/kg bolus, 60–120 μg/kg/h continuous infusion) result in preemptive analgesic effects that can reduce postoperative opioid usage with no adverse effects. [12,18] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal dose and infusion timing of ketamine for postoperative pain control has not yet been established; however, most trials have used ketamine in subanesthetic doses during the perioperative period. [18] Reviews and meta-analyses that have evaluated the preemptive analgesic effects of ketamine for postoperative pain have concluded that subanesthetic doses of ketamine (0.15–0.5 mg/kg bolus, 60–120 μg/kg/h continuous infusion) result in preemptive analgesic effects that can reduce postoperative opioid usage with no adverse effects. [12,18] …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the incidence of PONV following thyroidectomy appears to be higher than with other surgeries. [18] …”
Section: Discussionmentioning
confidence: 99%
“…In the long term, this aims to reduce the postoperative analgesic requirements. 9 After the afferent nociceptive impulses arrive at the spinal cord, the CNS sensitization occurs. The receptor responsible for pain memory is the NMDA receptors.…”
Section: Ketamine and Preemptive Analgesiamentioning
confidence: 99%
“…Di antara Modalitas preemptive analgesia yang ada, NMDA reseptor antagonis merupakan salah satu terapi yang efektif untuk mencegah perkembangan nyeri akut menjadi nyeri kronik. 5 Ketamin adalah noncompetitive nmda reseptor antagonis yang pertama kali disintesis pada tahun 1963 yang digunakan sebagai agen anestesi dan analgesi, mudah didapat,dan harga yang murah. Dosis ketamin yang direkomendasikan untuk preemptive analgesia adalah antara 0,075 mg/kgbb sampai dengan 0,5 mg/kgbb dan rekomendasi yang lain menyebutkan 0,15-0,25 mg/kgbb.…”
Section: Pendahuluanunclassified